The Origins and Evolution of Recent RNA Viruses: MERS, SARS, and COVID-19 and their Impact on Human Health, Longevity, and Global Healthcare - Einstein, George P.; Tulp, Orien L. (New Advances in Medicine and Medical Science Vol. 4, 2023)
The purpose of the present editorial perspective is to briefly review the evolution and development of the recently emerged coronaviruses. The disease was given the name coronavirus disease 2019 (COVID-19), spread internationally in what appeared to be an exponential fashion, and was quickly determined by the World Health Organisation (WHO) to have become a pandemic within the first few months of its discovery and emergence. Public health and scientific organizations are engaged in a continued international effort to uncover the confirmed origins of SARS-CoV-2, which is deemed essential to preventing future pandemics. Unfortunately, because the origins of the SARS-CoV-2 have not yet been identified, misleading and unverified allegations have been made about NIAID, EcoHealth and other entities that supported research on naturally occurring bat populations. One of the unsettling findings about COVID-19 is that individuals who were infected with SARS-CoV-2, the prevalence of which some researchers put as high as 40%, can spread the virus to others while asymptomatic, before they manifest overt symptoms, or even without ever showing any signs of illness. The virus may infect numerous tissues and organs after infection, including the brain, cardiovascular system, lungs, and other organs, and may result in long-lasting consequences. The NIH National Institute of Allergy and Infectious Diseases (NIAID) COVID-19 and others in cooperation with vaccine manufacturers research efforts have built upon earlier research on severe acute respiratory syndromes (SARS) and Middle East respiratory syndrome (MERS), also caused by strains of respiratory prone coronaviruses. Only time can reveal if the naturally occurring Omicron variant may unwittingly provide the key chapter that may bring the COVID-19 pandemic to its long-sought climax.